Anticancer and antiproliferative activity of ruthenium complex (II) bearing 3,3'-dicarboxy-2,2'-bipyridine ligand - Mohamed Saadh (Pensoft Publishers, 2023)
Even though significant progress has been made in cancer treatment, there is always room for improvement. The experimental drug Ruthenium Complex II shows promise as a cancer treatment. In this article, the dichloro-3,3'-dicarboxy-2,2'-bipyridyl bis(dimethylsulphoxide)ruthenium(II) [RuCl2(3,3'-dcbpy)(DMSO)2], have been synthesized, characterized, and studied for its anticancer activity against MDA-MB-231 and MRC-5 cell lines, as well as its mechanisms of action and selectivity. According to research, [RuCl2 (3,3'-dcbpy)(DMSO)2], is highly cytotoxic to the MDA-MB-231 and minimum cytotoxic to MRC-5 cell lines, with IC50 values of 5.95 and 579.6 μg/ml, respectively. Ruthenium Complex II is exceptionally effective at destroying cancer cells while causing minimal harm to healthy cells. RuCl2(3,3'-dcbpy)(DMSO)2] caused apoptosis, which was confirmed by the activation of caspase-3. Ruthenium complexes hold great promise as powerful anticancer agents. Their unique mechanisms of action, ability to selectively target cancer cells, and versatility in chemical structure make them attractive candidates for the development of targeted therapies.